2-Amino-4-(4-methoxyphenyl)-5-oxo-4H,5H-pyrano[3,2-c]chromene-3-carbonitrile acetic acid monosolvate - Bimal Bhushan Chakraborty; Saurav Paul; Siddique Anwar; Sudip Choudhury (IUCrData, 2023)
In the title co-crystal, C20H14N2O4·C2H4O2, the expected proton transfer from acetic acid to amine has not occurred. In the crystal, the chromene molecules are linked by N—H...O and N—H...N hydrogen bonds to generate [100] columns. The acetic acid molecules form inversion dimers linked by pairwise O—H...O hydrogen bonds and occupy voids between the columns.